2015
DOI: 10.1186/s40064-015-1549-7
|View full text |Cite
|
Sign up to set email alerts
|

Key information providers, channels, and characteristics of Japanese consumers’ informed choices of over-the-counter medications

Abstract: People need reliable information regarding over-the-counter medications (OTCs), so that they can independently make appropriate informed choices. The study aimed to identify the information providers and channels that have an impact on the purchase of OTCs, and to demonstrate the information needs of OTC purchasers, using these providers and channels, from the viewpoint of information characteristics such as specialty, objectivity, concreteness, comprehensiveness, individuality, and availability, focusing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Pharmacists are able to partially help in achieving these objectives. Previous studies showed that the recommendations of pharmacists most often affect the choice of OTC medications by patients 17,24,25. A nationwide survey conducted in Germany reported that pharmacies were the most common place where patients visited to obtain information about OTC medications 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists are able to partially help in achieving these objectives. Previous studies showed that the recommendations of pharmacists most often affect the choice of OTC medications by patients 17,24,25. A nationwide survey conducted in Germany reported that pharmacies were the most common place where patients visited to obtain information about OTC medications 26.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the recommendations of pharmacists most often affect the choice of OTC medications by patients. 17 , 24 , 25 A nationwide survey conducted in Germany reported that pharmacies were the most common place where patients visited to obtain information about OTC medications. 26 A systematic review by Raynor et al reported that patients preferred information about OTC medication tailored to their individual health conditions and illness by pharmacists to that prepared by manufacturers according to strict regulations.…”
Section: Discussionmentioning
confidence: 99%
“…But people need reliable information concerning OTC medicines to make appropriate decisions (Hayashi, Masuda, & Kimura, 2015). Therefore, the paper focuses on the sources of information used by teenagers and their influence on their attitudes toward OTC drugs.…”
Section: The Decision-making Process Of Self-medication With Otc Medimentioning
confidence: 99%
“…For each of the factors mentioned above, we used certain statements, which are theoretically based on the results of previous research and which are adjusted accordingly. In this way, the perceived risk was evaluated by the first 7 findings, which are adjusted accordingly (Almalak et al, 2014), the pharmacist expertise was analyzed by responding to statements 8-12 (adapted according to Kwan et al, 2008, Piecuch et al, 2013; advertising campaigns were evaluated through the statements 13-16 (Haddad et al, 2013, Hayashi et al, 2015, consumers' price sensitivity through statements 17-20 (Lodorfos et al, 2006), aspects relating to the purchase of OTC products through statements 21-24 (Shohel et al, 2013), while the last four conclusions concern consumer loyalty (Marinković, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The research shows that pharmacists are mostly perceived as the most significant carriers of information about these products, which supports the idea that their adequate training is very important for the realisation of these products, as well as consumer satisfaction. Moreover, it has been determined that pharmacists are the most common source of information, and they are those who determine the decision of the consumer and have a positive effect on their readiness to complete the purchase (Hayashi et al, 2015). The emergence of consumer dissatisfaction, when it comes to the advisory role of the pharmacist, mostly refers to the lack of the needed information (Villako et al, 2012).…”
Section: Pharmacist Expertisementioning
confidence: 99%